ANALYSIS OF THE INFLUENCE OF STAR DELTA SYSTEM IN REDUCE ELECTRIC STARTING SURGE IN 3 PHASE MOTORS - Hardine, Linkha; Dian Budhi Santoso; Ridwan Satrio Hadikusuma (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
Operations in the industry today use induction motors. There are several types of induction motors, one of which is a 3-phase induction motor. In the use of a 3-phase induction motor, there are several problems at the beginning, one of which is that there is a current surge in the starting received by the windings or rotor of a 3-phase induction motor which will cause damage to the motor windings. In previous research, research has been carried out to reduce electric starting spikes in 3 phase motors by lowering the frequency in a study entitled